Pilot Randomized Controlled Trial of Diabetes Group Prenatal Care - Carter, Ebony B.; Barbier, Kate; Hill, Pamela K.; Cahill, Alison G.; Colditz, Graham A.; Macones, George A.; Tuuli, Methodius G.; Mazzoni, Sara E. (American Journal of Perinatology, 2020)
Objective This study aimed to determine the feasibility and effectiveness of Diabetes Group Prenatal Care to increase patient engagement in diabetes self-care activities.Study Design A pilot randomized controlled trial was conducted at two sites. Inclusion criteria were English or Spanish speaking, type 2 or gestational diabetes, 22 to 34 weeks of gestational age at first study visit, ability to attend group care at specified times, and willingness to be randomized. Exclusion criteria included type 1 diabetes, multiple gestation, major fetal anomaly, serious medical comorbidity, and serious psychiatric illness. Women were randomized to Diabetes Group Prenatal Care or individual prenatal care. The primary outcome was completion of diabetes self-care activities, including diet, exercise, blood sugar testing, and medication adherence. Secondary outcomes included antenatal care characteristics, and maternal, neonatal, and diabetes management outcomes. Analysis followed the intention-to-treat principle.Results Of 159 eligible women, 84 (53%) consented to participate in the study and were randomized to group (n = 42) or individual (n = 42) prenatal care. Demographic characteristics were similar between study arms. Completion of diabetes self-care activities was similar overall, but women in group care ate the recommended amount of fruits and vegetables on more days per week (5.1 days/week ± 2.0 standard deviation [SD] in group care vs. 3.4 days ± 2.6 SD in individual care; p < 0.01) and gained less weight per week during the study period (0.2 lbs/week [interquartile range: 0–0.7] vs. 0.5 lbs/week [interquartile range: 0.2–0.9]; p = 0.03) than women in individual care. Women with gestational diabetes randomized to group care were 3.5 times more likely to have postpartum glucose tolerance testing than those in individual care (70 vs. 21%; relative risk: 3.5; 95% confidence interval: 1.4–8.8). Other maternal, neonatal, and pregnancy outcomes were similar between study arms.Conclusion Diabetes group care is feasible and shows promise for decreasing gestational weight gain, improving diet, and increasing postpartum diabetes testing among women with pregnancies complicated by diabetes.Key Points
Keywords: gestational diabetes; type 2 diabetes; group care; prenatal care